Planning and support materials in teaching story comprehension from the interbehavioral approach - Ana Cristina Mascareño Bórquez; Aldo Bazán-Ramírez; Néstor Miguel Velarde Corrales (Interacciones)
Despite the latest changes in educational reforms within the country, curriculum plans and ongoing program renewals aimed at resolving the educational gap reflected in national statistics, the results remain unfavorable. This leads to reflection and analysis to generate and implement new forms and teaching strategies. The purpose of this paper is to present the design of an alternative proposal for planning and the development of support materials, developed according to the second block of sixth grade primary education, in two expected learning contained in the formal basic education curriculum. Centered on the interaction in teaching-learning and according to different levels of functional aptitude. Subsequently it underwent a process of piloting and revision by experts to prove the pertinence of the planning and precisions for its implementation. As results, the support materials and the planning proposal are presented and discussed with the authors who have worked on planning proposals from the inter-behavioral approach.